Burden of non-communicable diseases and associated risk factors in rural areas of Jharkhand - Bharath Jagadeesh, (International Journal Of Community Medicine And Public Health, 2023)
Background: Non-communicable diseases (NCDs) are becoming a greater burden in India. The onset of NCDs occurs ten years earlier (around age 45) in India than it does in many developed nations. This study was conducted in 5 blocks of East Singhbhum and Saraikela-Kharsawan districts of Jharkhand to determine the prevalence of diabetes and hypertension in the rural population. Methods: Community based cross sectional study was conducted between April 2022 to Jan 2023 among individuals residing in rural areas of Jharkhand using multi-stage sampling with a sample size of 4579 individuals, who were 30 years and above. Results: Prevalence of diabetes amongst the study population was 16.3% (750) and prevalence of hypertension amongst the study population was 21.3% (977). Conclusions: High prevalence of non-communicable diseases such as diabetes and hypertension increase the burden on existing health care system. Primary prevention using health education, lifestyle modification etc. and secondary prevention using early diagnosis by screening in the community and referral to nearby health centers for treatment prevents the complications of NCDs.